2021
DOI: 10.3390/cancers13061476
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for ALK-Rearranged Non-Small Cell Lung Cancer: Challenges Inform Promising Approaches

Abstract: Rearrangements in the Anaplastic Lymphoma Kinase (ALK) gene have been implicated in 5–6% of all non-small cell lung cancers. ALK-rearranged non-small cell lung cancers are sensitive to ALK-directed tyrosine kinase inhibitors, but generally resistant to single-agent immune checkpoint inhibitors. Here, we aim to describe the mechanisms of ALK aberrations in non-small cell lung cancer by which an immunosuppressed tumor microenvironment is created, leading to host immune evasion. We report pre-clinical and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Other ALK inhibitors are in development, including repotrectinib (TPX-005), that may represent an effective therapeutic option for patients with ALK-rearranged NSCLC who have progressed on earlier-generation TKIs ( 23 ). Furthermore, the role of immune checkpoint inhibitors in ALK-positive NSCLC resistant to ALK-TKIs and chemotherapy is still under investigation ( 24 ). Finally, questions regarding the efficacy of treatments in sequential use were not investigated and, therefore, remain a subject for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other ALK inhibitors are in development, including repotrectinib (TPX-005), that may represent an effective therapeutic option for patients with ALK-rearranged NSCLC who have progressed on earlier-generation TKIs ( 23 ). Furthermore, the role of immune checkpoint inhibitors in ALK-positive NSCLC resistant to ALK-TKIs and chemotherapy is still under investigation ( 24 ). Finally, questions regarding the efficacy of treatments in sequential use were not investigated and, therefore, remain a subject for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the heterogeneity in data collection may be a drawback in massive assessment of data. In respect to this, it is noteworthy that previous studies concerning the role of some gene fusions, notably according to the partners, in resistance to immunotherapy associated with late‐stage NS‐NSCLC led to discrepant results 14–16 . This will certainly be a crucial issue in the future when making decisions on first‐line treatments targeting a gene fusion (notably in other genes than ALK and ROS1 ), probably for any stage and histological subtype of NSCLC patients.…”
Section: Technical Aspects Of Gene Fusion Detection In Lung Cancer: T...mentioning
confidence: 99%
“…These genomic alterations are sensitive to different molecules, notably to next‐generation TKIs (such as alectinib, brigatinib, and lorlatinib), which if given upfront result in significantly longer survival compared to initial treatment with the first‐generation inhibitor crizotinib or chemotherapy 9,11–13 . Excluding presence of an ALK fusion is also crucial before starting immunotherapy, due to the lack of efficacy and increased toxicity of the immune checkpoints inhibitors (ICIs) in ALK‐ positive NSCLC patients 14–16 . Besides a very low tumor mutational burden of ALK ‐positive tumors, uniquely below 3 mut/MB on average, 17 an immunosuppressive tumor microenvironment also appears to contribute to the inherent ICI resistance of these tumors 18 .…”
Section: Alk Ros1 Ntrk and Ret Fusions: The “Big Four” Fusion Targets...mentioning
confidence: 99%
“…A recent retrospective study revealed that approximately 10% of ALK-positive patients responded to immunotherapies [191]. Combination of ALK inhibitors and immunotherapy seems to show efficacy but some patients developed severe hepatotoxicity, and long-term clinical outcomes have not yet been reported [192,193]. Therefore, further studies are needed to identify effective immunotherapy and its combination with chemotherapy to achieve favorable clinical outcome for patients with ALK gene rearrangements.…”
Section: Eml4-alkmentioning
confidence: 99%